The Role of Open Innovation, and the Performance of European Union Regions - Lopes, João M. (2021)
This research aims to detect the factors that best explain the performance of regional innovation in the European Union (EU), in the year 2019, and compare the obtained results with the factors used to elucidate the performance of regional innovation in the EU during the year 2016. This comparison allowed us to identify the variations that have occurred during these 3 years. The methodology used is quantitative and served to identify the factors that clarify the performance of regional innovation in the EU in 2019. The data collected was treated in the econometric software Eviews10. Estimations used a multiple linear regression method. The attained results show that with the implementation of the Research and Innovation Strategy for Smart Specialization (RIS3), the Leader and Strong Regions benefited from its implementation. On the other hand, Moderate and Modest Regions failed to improve their innovative performance with the implementation of RIS3. On the practical contributions, it provides suggestions to the actors of the triple helix (Academy– Government–Industry) to improve the performance of innovation. Furthermore, it contributes to the theory by updating the knowledge of the existing literature with new dimensions from the 2019 RIS database. This research is original as it allows to appraise the evolution of the open innovative performance of the regions, by using comparative data from 2019 and 2016.